The Influence of Role Play on Students' English Speaking Skill at Nine Graders - Puspitorini, Ferawaty ((JELE) Journal Of English Language and Education, 2018)
This research investigates the influence of using role-play as teaching technique in teaching English speaking at ninth grade students of SMP NEGERI 9 BEKASI. There are two variables, they are teaching technique of role-play as independent variable and students’ speaking skill as dependent variable.The population consists of 62 students from all classes (2 classes). This research used population sample because the amount of sample is same with the amount of population. By simple random sampling technique, the writer determined 1 class as experimental class and the other class as control class. The research method used quasi experimental research. The research design used post test only. Instruments consist 3 indicators with 4 sub indicators for each. Test used oral technique of students speaking skill in role-play.The result of instrument test is validity. it determines higher than 0,275 of pearsons correlation standard. The instrument is also reliability. It determines higher than 0,5000 of alpha scale. The normality test with Kolmogorov-Smirnov is lower than 0,240. it means that the population is normality. The result of hypothesis test with R-square is 0,743. It determines that the influence is 74,3 % by using role-play technique. The writer concludes that there is significant influence of using role-play towards students’ English speaking skill at ninth grade of SMP NEGERI 9 BEKASI. Keywords: Role play, Speaking Skill